KOMUNIKASI INTERPERSONAL DALAM MENINGKATKAN MOTIVASI KARYAWAN DI MASA PANDEMI COVID-19 - Renika Yuliana; Dedi Rianto Rahadi (Magister Manajemen STIE Bank BPD Jateng, 2021)
In the current pandemic, the habit of personal face-to-face communication and contact with each other is no longer a priority. Communication at this time is very intense, causing individuals to send unclear speech and information, which leads to decreased psychological and motivational qualities. The method used is literature study method. The library research method is a collection of activities related to collecting library data, reading and taking notes, as well as methods of determining research materials (Zed, 2008: 3). In conclusion, communication turns out to have a good effect on increasing one's motivation. Therefore, in communication, accuracy, skill and caution are needed so that the motivation that is formed can meet the expected goals.